2021
DOI: 10.2147/rmhp.s324095
|View full text |Cite
|
Sign up to set email alerts
|

Successful Aging Among Community-Dwelling Older Adults in Urban Areas of Liaoning Province: The Crucial Effect of Visual Ability

Abstract: Purpose: Successful aging is an effective approach to coping with population aging; however, the definition and associated factors vary due to culture and demographic distribution differences. This study was designed to assess successful aging of the older adults in China and explore the associated factors. Methods: A community-based cross-sectional study was performed in Liaoning, China. After double-cognitive function screening, 3558 older adults (1656 males and 1902 females) ≥65 years of age served as our s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
3
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 28 publications
0
3
0
Order By: Relevance
“…Among several health-related factors in the microsystem, hearing, self-rated health, and life satisfaction all had an impact on successful aging among empty-nesters. First, the hearing function is associated with successful aging in empty-nesters, consistent with the findings of Liu et al [7]. WHO data in 2018 showed that hearing disability has become the most common type of disability in the elderly, and about one-third of the elderly aged 65 years and over worldwide have disabling hearing impairment [35].…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Among several health-related factors in the microsystem, hearing, self-rated health, and life satisfaction all had an impact on successful aging among empty-nesters. First, the hearing function is associated with successful aging in empty-nesters, consistent with the findings of Liu et al [7]. WHO data in 2018 showed that hearing disability has become the most common type of disability in the elderly, and about one-third of the elderly aged 65 years and over worldwide have disabling hearing impairment [35].…”
Section: Discussionsupporting
confidence: 79%
“…The evolving perspectives on aging have shifted from "how to live longer" to "how to age well", and the definition of successful aging has been perceived as a useful tool for describing the health status of the elderly population [4]. Since the concept of successful aging was introduced in 1961 by Havighurt, it has been explored by many scholars [5][6][7][8], but there is still no unified definition. Currently, the Rowe and Kahn model [9] is widely used, which defines successful aging as the absence of disease and disability, good physical and cognitive functioning, and active social participation.…”
Section: Introductionmentioning
confidence: 99%
“…The missing data would be handled only if the missing rate was >5%. 21 In this study, no missing data needed to be handled. SAS for Windows, V.8.2, was used to perform data analysis.…”
Section: Methodsmentioning
confidence: 99%
“…The detail study design has been previously described. 21 All men (n=2221) who were ≥65 years of age, were not diagnosed with dementia, lived in the local area for >5 years and could be persuade to take part in this study, comprised our study population. This study population accounted for 26.5% of the Chinese older men who had lived in the sampled communities for >0.5 year and left for <0.5 year.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation